A high-efficiency road energy harvester based on a chessboard sliding plate using semi-metal friction materials for self-powered applications in road traffic. (1st June 2018) - Qi, Lingfei; Pan, Hongye; Bano, Shehar; Zhu, Miankuan; Liu, Jizong; Zhang, Zutao; Liu, Yujie; Yuan, Yanping
Highlights: A novel road energy harvester based on a chessboard sliding plate is presented. SMFMs is used to make the chessboard sliding plate for well absorbing energy. This energy harvester is used for self-powered applications in road traffic. Efficiencies of 62.38% and 57% can be obtained in the simulation and experiments. Abstract: To explore the alternative resources of traditional energy, ambient-energy scavenging technologies have attracted worldwide attention. In particular, the roadways contain a significant potential for environmental energy harvesting (EEH). In this study, we proposed an innovative road energy harvesting system based on a chessboard sliding plate by using semi-metal friction materials (SMFMs) for collecting the mechanical energy induced by running vehicles. The SMFMs have good frictional properties that enable them to absorb energy well. The proposed system consists of four main components as follows: chessboard sliding plate module, transmission module, micro-generator module and energy storage module. Acting as the energy input mechanism, the chessboard sliding plate module harvests the kinetic energy produced by the friction between the wheel and chessboard plate. The transmission module converts the linear reciprocating motion of the chessboard sliding plate to unidirectional rotation of the input shaft of generator. The energy storage module stores the electric energy generated by the generator module in a supercapacitor. The performance of the proposed system is evaluated through dynamic simulations; the simulation results demonstrate that the system possesses rapid response. Efficiency of 62.38% and 57% are obtained in the simulation and experiments, respectively, validating that the proposed road energy harvesting system is feasible and practical for self-powered applications in road traffic electrical equipment, such as traffic lights, street lamps and speed measuring radar.